Choices of Ibn Hisham al-Ansari (d. 761 AH) in the Nawasikh al-Ibtidah: His Minor and Major Entourage as a Model - Abbas, Mithaq Ali; Mahmoud, Hussein Nouri (Journal of Tikrit University for Humanities, 2023)
The study deals with linguistic and idiomatic choices as they are clarified by the definition of Ibn Hisham al-Ansari. This topic is tackled according to the following: choosing the diacritic mark of hamza in the place of reasoning, and adding an initial justifying letter to the predicate. The study further elaborates on comparative verbs and nouns following such verbs. The study ends with its most important findings and the sources upon which it relied heavily to examine the topic.